The politics of confronting violence against women: conceptions of a nursing team - Maria Nazaré Souza dos Passos; Flávia Nataly Pereira da Silva Rocha; Naelia Vidal de Negreiros Silva; Marília Gabrielle Santos Nunes (Universidade de Pernambuco, 2022)
Objective: To identify the knowledge of the nursing team about the conceptions and actions of the policy to combat violence against women. Method: It is characterized as field research, developed in a public hospital of high complexity of maternal and child care in the city of Recife/PE. In which, descriptive and inferential analysis using the chi-square test. Results: It was evidenced that 70% of the team claims to know the policy, but 55% do not know or do not consider the cases as compulsory notification and 71% do not know how to deal with it. Conclusion: The team's difficulty regarding the policy to combat violence against women is notorious, where the lack of training contributes to this obstacle. be minimized with detailed recording.